Dynamical complexities in a tri-trophic hybrid food chain model with Holling type II and Crowley–Martin functional responses - Upadhyay, R. K. K.; Raw, S. N. N.; Rai, V. (Nonlinear Analysis: Modelling and Control, 2010)
We study how predator behavior influences community dynamics of predatorprey systems. It turns out that predator behavior plays a dominant role in community dynamics. The hybrid model studied in this paper reveals that period-doubling and period-doubling reversals can generate short-term recurrent chaos (STRC), which mimics chaotic dynamics observed in natural populations. STRC manifests itself when deterministic changes in a system parameter interrupt chaotic behavior at unpredictable intervals. Numerical results reinforce an earlier suggestion that period-doubling reversals could control chaotic dynamics in ecological models. In ecological terms, the prey and intermediate predator populations may go to extinction in the event of a catastrophe. The top predator is always a survivor. In contrast to this, this is not the case when the constituent populations are interacting through Holling type II functional response. Even this top predator can go to extinction in the event of such catastrophes.